Outcome of sentinel lymph node biopsy in early-stage squamous cell carcinoma of the oral cavity with methylene blue dye alone: a prospective validation study. Issue 8 (October 2019) - Vishnoi, J.R.; Kumar, V.; Gupta, S.; Chaturvedi, A.; Misra, S.; Akhtar, N.; Agarwal, P.; Jamal, N.; Pareek, P.
Abstract: Our aim was to evaluate the feasibility and role of sentinel lymph node (SLN) biopsy using methylene blue dye alone in identifying occult lymph node metastases in early oral cancer (cT1, T2, and cN0). The study was done from 2013–15 in 94 patients in a large cancer centre. The blue nodes were dissected and sent for frozen section, routine histopathological examination, and immunohistochemical testing for cytokeratin, and was followed by elective neck dissection in all patients. The identification rate was 93.61%. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy for frozen section and haematoxylin and eosin (H&E) staining were 84.6%, 100%, 100%, 93.9% and 95.5%, respectively. Occult lymph node metastasis was seen in 27.6% cases. Biopsy of SLN with blue dye alone might be used successfully with good sensitivity and negative predictive value in countries with limited resources in the developing world. Immunohistochemistry contributes to it by increasing the sensitivity and NPV, and thereby improves the diagnostic value.